Definitive chemoradiotherapy for cervical cancer: A 11‐year population‐based study. (15th January 2020) - Kalampokas, Emmanouil; Macdonald, Graham; Young, Helena; Bednarek, Antonina; Kennedy, Ann‐Marie; Cairns, Mary; Parkin, David E.
Abstract: Purpose: To assess the recurrence pattern and survival in women treated with definitive chemoradiotherapy for cervical cancer. Methods: A retrospective cohort study of women FIGO (2012) stage IB2 to IVA from the Grampian region of Scotland between February 2000 and March 2011. These women were followed up until April 2018. Results: A total of 121 eligible women allocated with mean age at treatment 50.59 years ( SD  = 13.98, range 22–82). Tumours staged: IB2: n  = 24 (19.8%), II: n  = 45 (37.2%), III: n  = 43 (35.5%) and IVA: n  = 7 (5.8%). Two (1.7%) women had no available data. Fifty‐five (45.5%) women had recurrence after treatment, and 51 (42.15%) women died from the disease. The sites of recurrence were as follows: central pelvic only ( n  = 4, 7.27%), pelvic and distant ( n  = 39, 70.91%) and distant only ( n  = 12, 21.82%) with median time from end of treatment to first recurrence 44 months (range 2–98), 26 months (range 1–146) and 22 months (range 3–66) respectively. 5‐and 8‐year overall survival was 76.0% (95% CI: 68.8%–84.0%) and 64.4% (95% CI: 56.4%–73.5%) respectively. Conclusions: Though overall survival is better than with radiotherapy alone, recurrence occurs up to 10 years after treatment. This raises the issues of how to reduce late recurrence and the appropriateness of current follow‐up protocols.